2017
DOI: 10.1159/000477520
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental Disomy of Chromosome 15 in Two Cases by Chromosome Microarray: A Lesson Worth Thinking

Abstract: Prader-Willi syndrome (PWS) and Angelman syndrome (AS) are neurogenetic disorders caused by loss of function of the imprinted genes at 15q11q13. A 5-7 Mb paternal/maternal deletion of chromosomal region 15q11.2q13 is the major genetic cause of PWS/AS, but in a small group of patients, the PWS/AS phenotype can result from maternal/paternal uniparental disomy (UPD) of chromosome 15. Various mechanisms leading to UPD include gametic complementation, trisomy rescue, and compensatory UPD, which can be inferred from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…If parental consanguinity were known prior to testing, it would be appropriate to pursue testing on a platform with SNPs. In addition, AOH such as that due to uniparental disomy (UPD) in 18C1493 is an aberration known to be disease associated 29 . Because UPD testing is only recommended if a clinically relevant chromosome (chromosomes 6, 7, 11, 14, 15, or 20) is involved in a prenatally detected chromosomal abnormality such as trisomy mosaicism 30 , this case could be pursued by additional testing 31 if such an event were identified by low-pass GS ( Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…If parental consanguinity were known prior to testing, it would be appropriate to pursue testing on a platform with SNPs. In addition, AOH such as that due to uniparental disomy (UPD) in 18C1493 is an aberration known to be disease associated 29 . Because UPD testing is only recommended if a clinically relevant chromosome (chromosomes 6, 7, 11, 14, 15, or 20) is involved in a prenatally detected chromosomal abnormality such as trisomy mosaicism 30 , this case could be pursued by additional testing 31 if such an event were identified by low-pass GS ( Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal microarray (CMA) is currently considered the firsttier diagnostic genetic test for neurodevelopmental disorders [14,15]. However, there remains a necessity for methylation analysis, especially for imprinting disorders, because CMA is not sufficient for diagnosis of these disorders [16]. We showed that MS-MLPA can not only diagnose PWS and AS, but also reveal the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of heterozygosity (AOH) is a well-recognized genomic change by which heterozygous alleles are absent rendering the sequence effectively homozygous. This homozygosity can result in human diseases including congenital 1 and somatic disorders 2 , 3 due to absence of wild-type alleles or biparental expression of an imprinted region. Although AOH can be a result of heterozygous or hemizygous deletions in the diploid genome, it can commonly manifest as copy-number neutral events which are also known as runs of homozygosity (ROH) or long contiguous stretches of homozygosity 4 .…”
Section: Introductionmentioning
confidence: 99%